Pensamientos y sentimientos ante el conflicto armado de un grupo de desplazados de Zarzal (valle) - Holguin Guzman, Juan Pablo; Montes Restrepo, Beatriz Elena (Universidad Antonio Nariño, 2022)
The purpose of this research is to know the thoughts and feelings that the victims of the armed conflict and who reside in the municipality of Zarzal have experienced. The interest of this project arises from the situation of violence that afflicts Colombia and how those who have been dispossessed of their lands, have lost loved ones and have had to flee abruptly from their properties have faced it. To interpret the information given by the interviewees, the theoretical postulates of Jhon Dewey are taken, the provisions of Law 1448 that corresponds to the Victims of the armed conflict in Colombia and investigative antecedents that address the emotional disorders consequent to this social problem. The methodology used is qualitative and a semi-structured interview was implemented to obtain the perceptions of the participants, concluding that the most significant thoughts are logical, creative, critical and reflective; as well as feelings of anger, frustration, resentment and hope.